Effect of Hot Rolling on Friction and Wear Characteristics of TiC Reinforced Copper-Based Metal Matrix Composites - S. Harish; R. Keshavamurthy; Dada Peer Basheer; Amith Kumar Gajakosh (Advances in Materials Science and Engineering)
The current study examines the effect of titanium carbide reinforcement (TiC) on the tribological behavior of copper metal matrix composites. The stir-casting process followed by hot rolling was employed to fabricate the composite parts. Hot rolling was performed at 510°C temperature with a 90% reduction ratio. An optical microscope, scanning electron microscope with energy dispersion spectroscopy, and Brinell hardness tester were used to investigate the microstructure, reinforcement particle distribution, and hardness. The microstructural investigations witness the uniform distribution of titanium carbide reinforcing agents along with the excellent binding with the copper matrix. The hardness was improved with the addition of titanium carbide content in both casting and rolling specimens. Dry sliding friction and wear tests were employed on a pin-on-disk setup with load values ranging from 30 to 120 N and sliding velocity values ranging from 0.628–2.512 m/s. In both casting and rolling conditions, the composites have a less coefficient of friction and wear rate than the matrix element. Wear rates of the unreinforced and reinforced cast and hot rolled alloys were enhanced as load and sliding velocity was raised. The incorporation of titanium carbide lowered the coefficient of friction and wear rate. In comparison to the unreinforced cast and rolled alloys, the coefficient of friction and wear of cast and rolled copper metal matrix composites was significantly reduced. Scanning electron microscopy was employed to investigate the worn surfaces and wear debris to confirm the possible wear mechanisms.